Firms and unemployment insurance take-up - Marta Lachowska; Isaace Sorkin; Stephen A. Woodbury (W.E. Upjohn Institute for Employment Research, 2022)
We use administrative data to quantify the firm role in unemployment insurance (UI) take-up. First, there are firm effects in both claiming and appeals, and, consistent with deterrence effects, these are negatively correlated. Second, low-wage workers are less likely to claim and more likely to have their claims appealed than median-wage workers, and firm effects explain a large share of these income gradients. Third, high-claiming and low-appealing firms are desirable firms: they are higher-paying and have lower separation rates. Finally, the dominant source of targeting error in the UI system is that eligible workers do not apply. Our findings emphasize a novel dimension of the role of firms in the labor market, and have implications for the financing of UI.
Keywords: H25; J63; J65; L20; 330; Unemployment insurance; take-up rates; UI claims; appeals; firm effects